Mycosis fungoides: Current trends in diagnosis and management - Panda Saumya (Wolters Kluwer Medknow Publications, 2007)
Mycosis fungoides (MF) is the most common group of cutaneous T-cell lymphomas. It is a rare non-Hodgkin′s lymphoma of mature, skin-homing, clonal, malignant T lymphocytes, usually observed in mid to late adulthood, that initially presents in the skin as patches, plaques, tumors, or generalized erythema (erythroderma) and can involve the lymph nodes and peripheral blood. Much progress has been made in recent years in understanding the origin of the malignant T cell in MF and the patho-physiology and immunology of the disease. This recent work has made a great impact on diagnosis, prognostication, and treatment. In this review, we survey the MF literature of the last decade and highlight the major trends.